Saepo Modi and Correlation among Statistical Methods for Measuring of Phenotypic Stability - Sabam Malau; Albiner Siagian; Maria Rumondang Sihotang; Rosnawyta Simanjuntak; N.D.M. Romauli Hutabarat (Jurnal Pertanian Tropik, 2019)
A stabile phenotype is desired. Many statistical methods are available to measure stability. So far, the choice of parameter of stability depended on the perception on the interaction of genotype and environment or ease of counting. The goal of this research was to study correlation among stability parameters. In total of 16 stability parameters were used in this research. Saepo modi (SMsp) as a stability parameter was also used. Branch rust incidence, leaf rust incidence, and leaf rust severity on Arabica coffee were used as variables. This research result showed that none of the parameters of stability correlated significantly with all parameter of stability. It coud be concluded that if someone want to use only one stability parameter, it is preffered to make use of regression and deviation from regression (D2i). In the case a researcher needs to use several of parameters of stability, Saepo modi (SMsp) might be exercised.